VARIABILITY AMONG YARD LONG BEAN HYBRIDS FOR POD CHARACTERS UNDER OPEN FIELD AND RAINSHELTER - FEBA VARGHESE; S. SARADA (The Bioscan, 2018)
Analysis of variance of ten yard long bean hybrids along with one commercial hybrid check (NS 634) for pod yield plant-1 and related characters viz., earliness to flowering, percentage fruit set, days to harvest and crop duration was carried out as two separate experiments in open field and rainshelter in order to identify hybrids suitable for open field and rainshelter cultivation. Hybrid VS 50 x VS 13 recorded maximum fruit set percentage under both open field and rainshelter (66.55 % and 56.80 % respectively), with VS 50 x VS 26 (55.27 per cent) and VS 34 x VS 50 (55.05 per cent) being on par in rainshelter. It was observed that the hybrid VS 34 x VS 50 recorded highest pod yield (1058.20 and 689.67 g plant-1) followed by hybrid VS 50 x VS 26 (973.27 and 674 g plant-1) under open field and rainshelter respectively. Hence, based on the observations, VS 34 x VS 50 and VS 50 x VS 26 were identified as best hybrids for both open field and rainshelter cultivation